Exploiting natural chemical photosensitivity of anhydrotetracycline and tetracycline for dynamic and setpoint chemo-optogenetic control - Armin Baumschlager (Nature Portfolio, 2020)
Anhydrotetracycline and tetracycline are commonly used chemicals to regulate transcription and translation, respectively. Here the authors exploit the natural photosensitivity of these molecules to place their activity under optical control.